(R)- and (S)-Proline-Derived Chiral Phosphoramides as Organocatalysts for the Enantiodivergent Aldol Reaction of Isatins with Cyclohexanone in the Presence of Water - Cruz-Hernández, Carlos; Hernández-González, Perla E.; Juaristi, Eusebio (Synthesis, 2018)
Novel organocatalysts derived from (R)- and (S)-proline and incorporating a chiral phosphoramide fragment were rationally designed and subsequently synthesized. These chiral compounds catalyze the enantioselective aldol addition reaction of cyclohexanone to prochiral isatins in the presence of water. These observations are particularly relevant since reports of asymmetric aldol reactions between cyclohexanone and isatins catalyzed by chiral secondary amines remain scarce, with primary amines being the most studied and successful catalysts. The present report includes a thorough evaluation of the new bifunctional catalysts that actually give rise to either enantiomer of the chiral product by proper selection of the configuration of the proline moiety.
Keywords: asymmetric organocatalysis; dual activation; hydrophobic interactions; Brønsted acids; Lewis bases